Empowering Society Through Digitalization of MSMEs During the Recession - Purwani, Diah Ajeng; Prasetyaningrum, Etika; Arfiani, Anindya Septiana (UI Scholars Hub, 2025)
One of the sectors and regions affected by the recession in Indonesia’s economic condition is Micro, Small, and Medium Enterprises (MSMEs) in Yogyakarta. Some of the problems that arise include a decrease in MSME turnover, which leads to a reduction in the number of employees. MSMEs need to maintain their businesses if they need to keep up with increasingly rapid technological developments in the online realm in their marketing strategies. The method used in this research is community-based research (CBR) based on cases in the field, which takes the MSME community as the research objective studied through digitalization on social media, especially Instagram. This study aims to discover how MSMEs can innovate in selling through online channels via social media, especially Instagram, to increase sales of these MSMEs. The media used is Instagram, so MSMEs can develop more in online marketing. The results of this research identify the formation of an Instagram social media account complete with the MSME logo and the structure of the Instagram feed used to increase sales during the recession. The empowerment that continues to synergize with various parties will be one of the strengths of developing MSMEs.